Stability of Biological Activity of Frozen β-lactams over Time as Assessed by Time-Lapsed Broth Microdilutions - Gleice Leite; Alexander Lawandi; Matthew P. Cheng; Todd Lee (MDPI AG, 2019)
To evaluate the antimicrobial agent’s stability stored at −80 °C, six β-lactams (meropenem, ertapenem, imipenem, ceftriaxone, ceftazidime, and piperacillin-tazobactam) were studied using the broth microdilution (BMD). The minimum inhibitory concentration (MIC) remained accurate with the same amount of frozen drug for at least six months. Thereafter, there was a diminishing drug concentration due to instability. At this temperature, most β-lactams can be frozen as a stock concentration for up to six months without a significant loss in antibiotic activity.